Analysis of Factors that Potentially Convert Nascent Entrepreneursfor Becoming Start up Business - I. , Solihin; V. , Silviani; N. , Ramadhan; A. , Andriani (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to analyze various factors that are considered important by start-up business people to get out of the nascent entrepreneur stage. These various factors are derived from the approach of entrepreneurial activity and the approach of entrepreneurial personality traits. The research method in this study used ex post facto research by asking questions to 30 start-up business people about what factors they are considered important when deciding to leave the nascent entrepreneur stage and become start-up business people. Based on this study, there are 9 very important factors that are thought to be the drivers of the entrepreneur's potential to become a start-up business.